Marketing - Roger A. Kerin (McGraw-Hill Irwin, 2009)
MARKETING: THE CORE, 3/e by Kerin, Hartley, and Rudelius continues the tradition of cutting-edge content and student-friendliness set by Marketing 9/e, but in a shorter, more accessible package. The Core distills Marketing's 21 chapters down to 18, leaving instructors just the content they need to cover the essentials of marketing in a single semester. Instructors using The Core also benefit from a full-sized supplements package that surpasses anything offered by the competition, while students will appreciate the easy-to-read paperback format that's equally kind to both the eyes and the pocketbook. The Core is more than just a baby Kerin